The Rise in Inequality after Pandemics : Can Fiscal Support Play a Mitigating Role? - Furceri, Davide (IMF Working Papers; Working Paper ;, 2021)
Major epidemics of the last two decades (SARS, H1N1, MERS, Ebola and Zika) have been followed by increases in inequality (Furceri, Loungani, Ostry and Pizzuto, 2020). In this paper, we show that the extent of fiscal consolidation in the years following the onset of these pandemics has played an important role in determining the extent of the increase in inequality. Episodes marked by extreme austerity-measured using either the government's fiscal balance, health expenditures or redistribution-have been associated with an increase in the Gini measure of inequality three times as large as in episodes where fiscal policy has been more supportive. We survey the evidence thus far on the distributional impacts of the COVID-19 pandemic, which suggests that inequality is likely to increase in the absence of strong policy actions. We review the case made by many observers (IMF 2020; Stiglitz 2020; Sandbu 2020b) that fiscal support should not be withdrawn prematurely despite understandable concerns about high public debt-to-GDP ratios.